Perluasan Kewenangan Komisi Penyiaran Indonesia Terhadap Pengawasan Media Digital - Moch. Marsa Taufiqurrohman; Jayus Jayus; A'an Efendi (The Constitutional Court of the Republic of Indonesia, 2022)
The problem of broadcasting is very complex, consisting of the definition and supervision of broadcasting which is still unclear and the authority of KPI is still weak to supervise digital media. The research objectives are: First, to look at the legal problems of the Indonesian Broadcasting Commission in supervising Digital Media. Second, the concept and practice of broadcasters on digital media surveillance in other countries. Third, the design of the Indonesian Broadcasting Commission's supervision of digital media supervision. The results of the study show that first, there are still legal problems with the position of KPI on digital media supervision. Second, digital media surveillance in Germany and Australia has been quite advanced which has strictly regulated broadcasting in digital with an integrated system. Third, the design is carried out by strengthening KPI institutions, institutional integration, and the